FEATURES OF INNOVATIVE ACTIVITY IN THE SPHERE OF TOURISM - Садыкова Рысты Каруевна,; Бикенова Айгуль Сериковна,; Елеусиз Ляйля Турсынкызы,; Темиралиева Зубайра Саулетовна, (Academic Journal of Physical and Chemical Sciences, 2019)
The authors of the article present the features of innovation activity in the field of tourism. The main reason for requiring the introduction of new technologies in the tourism sector is globalization processes that spawn the processes of standardization and unification of national cultures, increase the demand not only for the tourist product, but also the peculiarities of different countries and regions, visiting which partly compensates for the lack of new impressions in the standardized modern the world. An important process that accompanies globalization is the merger and concentration of tourism firms, the formation of large transnational conglomerates in the field of tourism. There is a need to bring disparate tourism into a single system to create a powerful industry that is able to accumulate cash to allocate significant revenues to the state budget and further intensive development of national tourism.